"I'm the King of Debt": Pastoral Reflections on Debt in the Age of Trump - Rogers-Vaughn, Bruce (Pastoral psychology, 2019)
During the chaos surrounding the first two years of the Trump presidency in the United States, what may be missed is the extent to which Trump is a marker of financial capitalism, with its compulsive dependency on the production of debt. In this essay, the author does not assess Trump personally but rather what he signifies with regard to financialization. He begins by documenting the phenomenal increase in household and total global debt that began during the onset of neoliberalization, as Trump was beginning his business enterprises. This debt has created a global economic and moral emergency. Second, the author discusses the central role of debt in financial capitalism and in the neoliberal ideology, or faith narrative, that justifies the debt system. Debt has become so foundational that it is transforming not only the economy but also culture, relationships, and subjectivity. This yields a new form of moral injury that is becoming pervasive. In the third move, he considers debt as a social, interpersonal, and psychological conundrum. Many mainline progressives are insistent that debt can be reformed and thus serve societies, communities, and individuals in beneficent ways. The author contends that the proposed reforms would likely spell the end of capitalism, an outcome these theorists generally wish to avoid. Furthermore, he points to evidence from psychoanalytic psychotherapy indicating that even relational, nonmonetized forms of indebtedness may prove to be interpersonally and psychologically damaging. Relational obligations, he notes, do not have to follow the logic of debt. Finally, the author contests Christian theological narratives that understand sin and salvation in terms of debt and debt forgiveness, and he points to an alternative approach within the history of Christian theology that holds promise given the current environment of toxic and insufferable debt.